DAMPAK PENERAPAN BIG DATA DALAM SISTEM INFORMASI MANAJEMEN TERHADAP PREDIKSI TREN DAN STRATEGI PEMASARAN KONSUMEN DI INDONESIA TAHUN 2025 - Nur Khadijah Wahyu Utami; Muhammad Irwan Padli Nasution (CV. Barokah Publsiher, 2025)
Rapid advances in information technology have triggered significant transformation in the business sector, especially in the development and application of Management Information Systems (MIS). One of the most notable changes in this digital era is the integration of Big Data, which reshapes how organizations interpret market patterns and consumer behavior. As companies increasingly rely on data-driven strategies, Big Data becomes a critical tool for forecasting future trends and designing competitive business models. This study seeks to analyze the impact of Big Data integration in MIS on predictive capabilities and marketing strategies within the Indonesian business context in 2025. Using a descriptive qualitative method supported by a literature review from 13 national and international journal sources, the research reveals that Big Data effectively enhances consumer analytics accuracy, improves decision-making efficiency, and supports more targeted and personalized marketing. Nevertheless, the implementation process faces several constraints, such as limited digital expertise, data integration difficulties, and concerns related to privacy, ethics, and cybersecurity. Therefore, this study concludes that the success of Big Data adoption relies not only on technological readiness but also on organizational capability, regulatory support, and a strong digital mindset.